2021
DOI: 10.2217/epi-2020-0341
|View full text |Cite
|
Sign up to set email alerts
|

miR-498 inhibits autophagy and M2-like polarization of tumor-associated macrophages in esophageal cancer via MDM2/ATF3

Abstract: Structured abstract Aim: To elucidate the effect of miRNA (miR)-498 on autophagy and M2-like macrophage polarization in esophageal cancer. Methods: Autophagy was evaluated in esophageal cancer. Macrophage markers specific for M1- or M2-like phenotype were determined. The binding relationships between miR-498 and MDM2, MDM2 and ATF3 were analyzed. Results: miR-498 was downregulated in esophageal cancer and was associated with disease-free and overall patient survival. Enhanced miR-498 reduced LC3I conversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…31 miR-498 inhibits M2 polarization of TAM by MDM2/ATF3. 32 miR-149 inhibits metastasis in breast cancer cells by limiting CSF-1-dependent recruitment and M2 polarization of macrophages. 33 In other words, our experiments revealed that miR-27a-3p targets the ATF3/ CSF-1 pathway to limit the development of NSCLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 miR-498 inhibits M2 polarization of TAM by MDM2/ATF3. 32 miR-149 inhibits metastasis in breast cancer cells by limiting CSF-1-dependent recruitment and M2 polarization of macrophages. 33 In other words, our experiments revealed that miR-27a-3p targets the ATF3/ CSF-1 pathway to limit the development of NSCLS.…”
Section: Discussionmentioning
confidence: 99%
“…Molecularly distinct tumours can be analysed by specific miRNA for cancer diagnosis, prognosis and treatment 31 . miR‐498 inhibits M2 polarization of TAM by MDM2/ATF3 32 . miR‐149 inhibits metastasis in breast cancer cells by limiting CSF‐1‐dependent recruitment and M2 polarization of macrophages 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that M2 macrophages play a preventive role in the progression of AS, the ATF3 activation appears to exert macrophage polarization into an anti-inflammatory phenotype in AS. However, Li et al recently proposed that the reduced M2-like polarization of macrophages mediated by miR-489 is associated with ATF3 deubiquitination through MDM2 ( 76 ). These findings suggest that ATF3 has a complex role in macrophage polarization.…”
Section: The Function and Molecular Mechanism Of Atf3 In Asmentioning
confidence: 99%
“…The study presented by Li and collaborators proves the role of miR-498 in the regulation of autophagy in M2 macrophages in esophageal cancer. In this model, the inhibition of MDM2 (mouse double minute 2 homolog)-mediated ATF3 (cyclic AMP-dependent transcription factor) degradation by miR-498 led to both autophagy and the suppression of M2 polarization [ 132 ].…”
Section: Promising Therapiesmentioning
confidence: 99%